Morfoanatomia e histoquímica de órgãos vegetativos foliares das espécies de solanum sect. Micracantha ocorrentes no brasil e um estudo farmacobotânico de Solanum jamaicense Mill. (Solanaceae) - Santos, Edinalva Alves Vital dos (2020)
Solanum sect. Micracantha belonging to the subgenus Leptostemonum is a Neotropical group, which is characterized by scandent shrubs or climbers species, aculeate, with flowers having stellate corolla and glabrous berries. A morphoanatomical and histochemical study on the leaves of six species of Solanum sect. Micracantha, occurring in Brazil, was carried out. Morover, a pharmacobotanical study was performed on vegetative organs of Solanum jamaicense Mill a species of ethnomedicinal interest. The study was performed on fresh, fixed and dry material, according to the usual techniques in plant anatomy. All samples were analyzed and micrographed under light microscopy and S. jamaicense Dunal also was analyyzed by scanning electron microscopy. As results, Solanum aturense and S. lanceifolium Jacq. showed hypoestomatic leaves with the anticlinal cell walls of epidermal cells straight on the adaxial surfaces, while the other species have amphystomatic leaves with the epidermal cells curved or sinuous. Anisocytic and anomotetracytic stomata were common to all species, however, paracytic stomata were also observed in S. leucopogon and S. monachophyllum Dunal. Heterogeneous dorsiventral mesophyll was a common pattern for all species, with the biconvex midrib having a single vascular bundle in S. jamaicense, S. lanceifolium Jacq. S. monhachophyllum and S. subineme,Jacq. 2—3 bundles in S. aturense and 3—5 in S. leucopogon. The shape of petiole is semicircular in all species, with adaxial projections in S. lanceifolium, S. leucopogon, S. monhachophyllum and S. subinerme. The vascular system is bicolateral with three bundles in S. lanceifolium and S. subinerme and five bundles in the other species. The pharmacobotanical study of S. jamaicense showed the secondary roots with circular shape with 3—4 layers of peridermis, the cortex is formed by aerenchyma; the vascular system is of the protostelic type; the stem has 2-layers of epidermis; the vascular system is symphonostelic amphyphloic; the leaf blade has sinuous anticlinal cell walls of the epidermis, and anisocytic, amphianisocytic and anomotetracytic stomata, and stellate, multiangulated, long stalked trichomes; epicuticular waxes in "crusts", "granules", "membranous platelets" and "coiled rodlets were observed on the both surfaces of epidermis; the margin is cuspidate; the midrib is biconvex with 1-vascular bundle; the petiole is semicircular with 2-layered epidermis with vascular system bicolateral, with five vascular bundles. The morphoanatomy of the six species studied showed the leaf morphology and the anatomy of the epidermis, stomata and trichomes as the main distinguishing characteristics, together with the vascularization of the midrib and petiole. The pharmacobotanical study of S. jamaicense revealed a set of diagnostic characters, mainly related to leaf morphology and the anatomy of the epidermis and its attachments and, mainly, by the cortical parenchyma of aerenchyma-type in the stem and roots, which can be used as an additional tool for the taxonomy of S. jamaicense, and also the quality control of its ethnodrugs